Development of a microfluidic photochemical flow reactor concept by rapid prototyping - Dinter, Robin; Willems, Suzanne; Nissalk, Thilo; Hastürk, Oguz; Brunschweiger, Andreas; Kockmann, Norbert (Frontiers in Chemistry, 2023)
The transfer from batch to flow chemistry is often based on commercial microfluidic equipment, such as costly complete reactor systems, which cannot be easily tailored to specific requirements of technologies such as DNA-encoded library technology (DELT), in particular for increasingly important photochemical reactions. Customized photoreactor concepts using rapid prototyping technology offer a modular, flexible, and affordable design that allows for adaptation to various applications. In order to validate the prototype reactors, a photochemical pinacol coupling reaction at 368 nm was conducted to demonstrate the transfer from batch to flow chemistry. The conversion rates were optimized by adapting the design parameters of the microfluidic flow photoreactor module. Subsequently, the photoreactor module has been extended to an application with DNA-tagged substrates by switching to LEDs with a wavelength of 454 nm. The successful recovery of DNA confirmed the feasibility of the modular-designed flow photo reactor. This collaborative approach holds enormous potential to drive the development of DELT and flow equipment design.